Frequency and electric field controllable photodevice: FYTRONIX device - Tataroglu, A.; Al-Sehemi, Abdullah G.; Ozdemir, Mehmet; Ozdemir, Resul; Usta, Hakan; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2017)
Al/p-Si/BODIPY/Al diode was fabricated by forming BODIPY organic layer on p-Si having ohmic contact. The electrical and photoresponse properties of the prepared diode were investigated in detail. The current-voltage ( I-V) measurements were performed under dark and various illumination intensities. It is observed that the photocurrent under illumination is higher than the dark current. The transient measurements indicate that the device exhibits both photodiode and photocapacitor behavior. We called this device as FYTRONIX device. The photoresponse behavior of the FYTRONIX device is controlled simultaneously by frequency and electric field. The FYRONIX device can be used as a photoresponse sensor in optoelectronic applications.
Keywords: BODIPY; Organic thin film; Photodiode; Photoresponse device